Transition From PCR-Ribotyping to Whole Genome Sequencing Based Typing of Clostridioides difficile - Seth-Smith, Helena M. B.; Biggel, Michael; Roloff, Tim; Hinic, Vladimira; Bodmer, Thomas; Risch, Martin; Casanova, Carlo; Widmer, Andreas; Sommerstein, Rami; Marschall, Jonas; Tschudin-Sutter, Sarah; Egli, Adrian (Frontiers in Cellular and Infection Microbiology, 2021)
Clostridioides difficile causes nosocomial outbreaks which can lead to severe and even life-threatening colitis. Rapid molecular diagnostic tests allow the identification of toxin-producing, potentially hypervirulent strains, which is critical for patient management and infection control. PCR-ribotyping has been used for decades as the reference standard to investigate transmission in suspected outbreaks. However, the introduction of whole genome sequencing (WGS) for molecular epidemiology provides a realistic alternative to PCR-ribotyping. In this transition phase it is crucial to understand the strengths and weaknesses of the two technologies, and to assess their correlation. We aimed to investigate ribotype prediction from WGS data, and options for analysis at different levels of analytical granularity. Ribotypes cannot be directly determined from short read Illumina sequence data as the rRNA operons including the ribotype-defining ISR fragments collapse in genome assemblies, and comparison with traditional PCR-ribotyping results becomes impossible. Ribotype extraction from long read Oxford nanopore data also requires optimization. We have compared WGS-based typing with PCR-ribotyping in nearly 300 clinical and environmental isolates from Switzerland, and in addition from the Enterobase database (n=1778). Our results show that while multi-locus sequence type (MLST) often correlates with a specific ribotype, the agreement is not complete, and for some ribotypes the resolution is insufficient. Using core genome MLST (cgMLST) analysis, there is an improved resolution and ribotypes can often be predicted within clusters, using cutoffs of 30-50 allele differences. The exception are ribotypes within known ribotype complexes such as RT078/RT106, where the genome differences in cgMLST do not reflect the ribotype segregation. We show that different ribotype clusters display different degrees of diversity, which could be important for the definition of ribotype cluster specific cutoffs. WGS-based analysis offers the ultimate resolution to the SNP level, enabling exploration of patient-to-patient transmission. PCR-ribotyping does not sufficiently discriminate to prove nosocomial transmission with certainty. We discuss the associated challenges and opportunities in a switch to WGS from conventional ribotyping for C. difficile.